Penguatan Tata Kelola Kawasan Konservasi Laut Melalui Integrasi Sistem Sosial Ekologis - Zulkifli Mappasomba; Permana Yudiarso; Muhammad Yusuf; Irwan dan Anugrah (Balai Besar Riset Sosial Eonomi Kelautan dan Perikanan, 2026)
Dengan hanya 35% Kawasan Konservasi Perairan (KKP) Indonesia yang diklasifikasikan efektif menurut standar IUCN, diperlukan pendekatan tata kelola yang mampu menjembatani tujuan ekologis dan sosial melalui integrasi Sistem Sosial‑Ekologis (SES). Penelitian ini merupakan tinjauan sistematis dan meta‑analisis atas 85 studi empiris periode 2005–2024 yang dipilih menggunakan prosedur PRISMA, dengan ekstraksi data terstandar dan perhitungan ukuran efek kumulatif (Hedges’ g) serta interval kepercayaan 95%. Integrasi SES pada KKP masih terbatas, meskipun banyak yang mengklaim adopsi, hanya 12% yang memenuhi indikator secara menyeluruh (ekonomi, sosial, dan ekologis). Secara agregat, strategi berbasis SES berasosiasi dengan perbaikan luaran ekologi dan sosial: peningkatan tutupan karang (≈25%), kenaikan biomassa ikan (≈40%), serta penurunan konflik tenurial hingga 55%. Analisis meta‑regresi mendukung ketepatan model integrasi (R² = 0,79) dan menunjukkan potensi peningkatan pendapatan rumah tangga pesisir sekitar Rp 1,2 juta per bulan (p < 0,01). Temuan ini menginformasikan rekomendasi kebijakan: harmonisasi regulasi lintas otoritas, penguatan kelembagaan berbasis komunitas yang adaptif, serta pengembangan platform pemantauan digital partisipatif, termasuk usulan Indeks Integrasi SES‑KKP sebagai alat diagnosis dan evaluasi. Integrasi SES yang kuat berasosiasi dengan peningkatan peluang keberhasilan pengelolaan KKP dan pengurangan pelanggaran di lapangan. Title: Strengthening The Governance of Marine Conservation Areas Through The Integration of Socio-Ecological Systems The management effectiveness of Marine Protected Areas (MPAs) in Indonesia remains a significant challenge; evidence shows that only 25% of MPAs are effectively managed, while 71% of coral reefs and 42% of seagrass meadows are in poor condition. This study aims to identify key barriers and validate an adaptive governance model based on Social- Ecological Systems (SES) for MPAs using a Systematic Review and Meta-Analysis (SRMA) approach in accordance with PRISMA protocols. The study is limited to empirical articles in Indonesia (synthesising cases from Raja Ampat and Wakatobi) published between 2015 and 2025 in reputable journals (Q1-Q2/Sinta 1-2). Data from 75 studies were analysed through content analysis based on Ostrom’s framework and meta-analysis (Hedges’ g and meta-regression) to measure variables including coral cover, fish biomass, and social conflict. The results demonstrate a large cumulative effect size (g = 0.82) and R² = 0.79, indicating that the application of SES principles explains 79% of the variation in management effectiveness. Ecologically, SES implementation increased coral cover by 25% and fish biomass by up to 40%. Socially, tenurial conflicts and violations were successfully reduced by 55%. The primary barriers identified in SES integration were tenurial conflicts (42%) and policy fragmentation (25%). To address these obstacles, this research proposes a “20-30-50” adaptive zoning model (core zone, sustainable fisheries zone, and collaborative zone) supported by the strengthening of customary institutions, community-based blue economy initiatives, and participatory digital monitoring. This model is proven to improve overall ecological and social indicators. Consequently, SES integration significantly enhances MPA effectiveness and coastal wellbeing. Recommendations include the harmonisation of sectoral regulations, the institutionalisation of polycentric adaptive governance, and the adoption of an SES-MPA index for sustainable monitoring.